2014
DOI: 10.1063/1.4894243
|View full text |Cite
|
Sign up to set email alerts
|

Terajets produced by dielectric cuboids

Abstract: The capability of generating terajets using 3D dielectric cuboids working at terahertz (THz) frequencies (as analogues of nanojets in the infrared band) are introduced and studied numerically. The focusing performance of the terajets are evaluated in terms of the transversal full width at half maximum along x-and y-directions using different refractive indexes for a 3D dielectric cuboid with a fixed geometry, obtaining a quasi-symmetric terajet with a subwavelength resolution of ~0.46λ0 when the refractive ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 22 publications
4
72
0
Order By: Relevance
“…4, it can be observed that the maximum value is obtained for the first cube while it is reduced for the rest. For this chain, the power enhancement (defined as the power at the output surface of each cube compared with the power without cubes) is 8.5, 11.6 and 10.8 (in linear scale) for the first, second and third cube, respectively, in good agreement with the results of a single cuboid 20 . Thus, it is observed that a mesoscale dielectric cube-air-chain waveguide is mainly characterized by the periodicity of jets corresponding to the optimal length of air-gap between cubes when a fixed geometry and materials respectively.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…4, it can be observed that the maximum value is obtained for the first cube while it is reduced for the rest. For this chain, the power enhancement (defined as the power at the output surface of each cube compared with the power without cubes) is 8.5, 11.6 and 10.8 (in linear scale) for the first, second and third cube, respectively, in good agreement with the results of a single cuboid 20 . Thus, it is observed that a mesoscale dielectric cube-air-chain waveguide is mainly characterized by the periodicity of jets corresponding to the optimal length of air-gap between cubes when a fixed geometry and materials respectively.…”
Section: Introductionsupporting
confidence: 76%
“…These results are not surprising since a change in  modifies the refractive index of the cubes and therefore a shift of the focus should occur 20 . Also the length of terajet is increased when increasing the loss tangent.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…23,24 The initial studies on terajet generation were based on spheroids and the well-known Mie scattering theory. 20,25,26 Later, researchers found out-both theoretically and experimentally-that cuboids can generate terajets 27 with some advantages over spheroid-generated terajets from the point of view of the imaging application, such as more symmetric hotspots. 23 The generation of terajets from the cuboid under planar illumination, which can be considered as an NA = 0 focusing device with the focal point at infinity, has been experimentally confirmed and verified in the THz frequency band; the obtained FWHM was 0.6λ.…”
Section: Introductionmentioning
confidence: 99%